The big picture - Leather, Sue (Cambridge English readers. Level 1, 2001)
Photographer Ken Harada thinks so when he gets a fantastic photo of a famous sumo star who is visiting Tokyo. However, it becomes clear that somebody wants that photo badly and will do anything to get it. Life suddenly becomes very dangerous for Ken and when he develops the photo he realises why.